2018
DOI: 10.1002/ange.201801912
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobicity Control in Adaptive Crystalline Assemblies

Abstract: Supportinginformation and the ORCID identification number(s) for the author(s) of this article can be found under: https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…26,78 For this purpose, we designed a simplified molecular version of common triblock copolymers, 79−81 molecular units are attached to the termini of a hydrophilic polymer (Figure 10a). 82 The films exhibited long-range order following deposition from aqueous solution, as detected by optical microscopy under crossed polarizers, with the dimensions of ordered domains extending over hundreds of micrometers (Figure 10b). X-ray diffraction (XRD) revealed that the film is crystalline, exhibiting sharp peaks (Figure 10c) typical of crystalline PEG.…”
Section: Crystalline Switching Of Hydrophobicitymentioning
confidence: 99%
“…26,78 For this purpose, we designed a simplified molecular version of common triblock copolymers, 79−81 molecular units are attached to the termini of a hydrophilic polymer (Figure 10a). 82 The films exhibited long-range order following deposition from aqueous solution, as detected by optical microscopy under crossed polarizers, with the dimensions of ordered domains extending over hundreds of micrometers (Figure 10b). X-ray diffraction (XRD) revealed that the film is crystalline, exhibiting sharp peaks (Figure 10c) typical of crystalline PEG.…”
Section: Crystalline Switching Of Hydrophobicitymentioning
confidence: 99%